Theoretical analysis of expanded porphyrins: Aromaticity, stability, and optoelectronic properties - Wei, Wei; Zhao, Zeng-Xia; Xia, Bao-Hui; Li, Wei (Frontiers in Chemistry, 2022)
Expanded porphyrin systems are capable of binding a variety of substrates due to their increased cavity size and aromatic nature, holding important application as magnetic resonance imaging contrasting agents and as sensitizers for photodynamic therapy. It is there of fundamental interests to know the photoelectrical properties of expanded porphyrins using quantum chemistry calculations. In this work, we theoretically designed and screened a series of expanded porphyrins by incorporating terthiophene (TTH) and dithienothiophene (DTT) moieties. Our calculations showed that all the designed molecules exhibit excellent optoelectronic performance than the reference molecule. It is suggested that the porphyrin molecule with TTH moiety has better stability than the one with DTT moiety. Finally, we demonstrated that molecule 2 features with TTH moiety and the inverted selenophene ring outperform other molecules because it exhibits increased HOMO-LUMO gap, planar geometry, and strengthened aromaticity. We expect that this work can provide theoretical guidelines for the design of novel porphyrin materials.